The Siderophore Piscibactin Is a Relevant Virulence Factor for Vibrio anguillarum Favored at Low Temperatures - Balado, Miguel; Lages, Marta A.; Fuentes-Monteverde, Juan C.; Martínez-Matamoros, Diana; Rodríguez, Jaime; Jiménez, Carlos; Lemos, Manuel L. (Frontiers in Microbiology, 2018)
Vibrio anguillarum causes vibriosis, a haemorrhagic septicaemia that affects many cultured marine fish species worldwide. Two catechol siderophores, vanchrobactin and anguibactin, were previously identified in this bacterium. While vanchrobactin is a chromosomally encoded system widespread in all pathogenic and environmental strains, anguibactin is a plasmid-encoded system restricted to serotype O1 strains. In this work we have characterized, from a serotype O2 strain producing vanchrobactin, a novel genomic island containing a cluster of genes that would encode the synthesis of piscibactin, a siderophore firstly described in the fish pathogen Photobacterium damselae subsp piscicida. The chemical characterization of this siderophore confirmed that some strains of V. anguillarum produce piscibactin. An in silico analysis of the available genomes showed that this genomic island is present in many of the highly pathogenic V. anguillarum strains lacking the anguibactin system. The construction of single and double biosynthetic mutants for vanchrobactin and piscibactin allowed us to study the contribution of each siderophore to iron uptake, cell fitness and virulence. Although both siderophores are simultaneously produced, piscibactin constitute a key virulence factor to infect fish, while vanchrobactin seems to have a secondary role in virulence. In addition, a transcriptional analysis of the gene cluster encoding piscibactin in V. anguillarum showed that synthesis of this siderophore is favoured at low temperatures, being the transcriptional activity of the biosynthetic genes three-times higher at 18 ºC than at 25 ºC. We also show that iron levels and temperature contribute to balance the synthesis of both siderophores.